PENGARUH KUALITAS LAYANAN DI WISMA WERDAPURA SANUR DI DENPASAR (sebelum dan sesudah pelatihan ) - Agung Permana Budi (Institut Pariwisata dan Bisnis Internasional, 2011)
Wisma Werdahapura currently in the introduction stage and has not gained much market share as long as this always depends on the segment of domestic guests are dominated by the government. The room occupancy rate for the first year target achieved was 50%, with average growth of 8.80% per year, then at the end of the five-room occupancy rate is expected to be achieved by 70%. In addition to the room occupancy rate to be achieved over the next five years, continues to increase, average daily room rate or the average room rate for the next five years are also targeted to increase.The following is in response to the findings of the research problem that was formulated in the form of conclusions. Front office services (X1), service-housekeeping procedures (X2), MICE services (X3), eating and drinking services (X4), recreation facilities and services (X5) affect customer satisfaction (Y) both before and after training at Wisma Werdapura , this is indicated by a significant degree on average close to 1 (one) in each variable.The training provides improved scores against the front office services (X1), service-housekeeping procedures (X2), MICE services (X3), eating and drinking services (X4), recreation facilities and services (X5) as shown by the average - average score before the given 2:44 while training for the training given an average score obtained by 4:12 indicates that training is an effective tool to improve service to customers so that customers become dissatisfied Keyword: Service Quality, Customer Satisfaction